GAMBARAN FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BENDUNGAN ASI PADA IBU NIFAS DI WILAYAH KERJA UPT PUSKESMAS PANCA MAKMUR TAHUN 2023: Description Of Factors Associated With The Events Of Asi Dams In Postpartum Mothers In The Work Area Upt Puskesmas Panca Makmur 2023 - Meri Anjalina, Baiq (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
The postpartum period is the most vulnerable period for morbidity, one of the causes of morbidity in postpartum mothers is problems with the lactation process. During the puerperium infection and inflammation of the breast can occur, infection occurs through wounds on the nipples, but maybe also through the blood circulation. The signs are chills accompanied by a rise in temperature, sufferers feel lethargic and have no appetite. The cause of the infection is usually staphylococcus aureus, enlarged breasts, breast pain in a place where the skin is red, swollen, and painful to touch. Therefore it is necessary to prevent one of them with breast care.The purpose of this study was to analyze the description of the factors associated with the incidence of breastfeeding in postpartum mothers in the working area of ??the UPT Panca Makmur Health Center, North Morowali Regency in 2023.This study uses a quantitative research method. The research design used in this study is a descriptive survey. Based on the total sampling technique, the number of samples obtained was 33 respondents. The results showed the characteristics of the respondents in terms of age, parity, education and occupation. The average number of respondents aged 25 to 30 years was 16 people (48.5%), while the parity of respondents was more dominant primipara and multipara as many as 13 people each (39.4%), for education more dominant high school graduates were 14 people (42.4%), and 17 people (51.5%) do not work for more dominant jobs. Factors related to breast milk retention include experience of breastfeeding, frequency of breastfeeding, technique of suckling, and shape of the nipples. Regarding breastfeeding experience, only 3 (9%) of mothers who had breastfed before experienced breast milk retention. While mothers who breastfeed more than 12 times, only 5 people (15%) experience breast milk retention. For proper breastfeeding techniques, only 7 people (21%) had normal nipple shapes, and only 1 person (3%) had breast milk.It is hoped that health workers can improve health services to the community, especially for women of reproductive age regarding postpartum health in dealing with breast milk dams during the postpartum period.